Restructuring Irish Higher Education - Hazelkorn, Ellen (International Higher Education, 2012)
Irish higher education is undergoing significant change. Some of these changes are driven by the economic crisis sweeping across Ireland and Europe. But other changes are arguably part of a wider paradigm shift affecting higher education around the world: the challenge of meeting rising demands for high-quality mass public higher education at a time of globalisation and accelerating competition. As higher education is seen as key to sustainable economic recovery, there is a move towards greater government steerage of both the HE and research system. Ireland presents an interesting case study.